Alberta's oil sands reclamation policy trajectory: the role of tense layering, policy stretching, and policy patching in long-term policy dynamics. Issue 10 (2nd October 2016) - Wellstead, Adam; Rayner, Jeremy; Howlett, Michael
Abstract : As the Canadian oil sands development matures, an increasingly important policy activity is reclamation. Reclamation has received limited attention compared with the broader discussion of oil sands expansion, however, and its past direction and future trajectory are unclear. Recent moves to reform the policy in Alberta have been interpreted simultaneously as a major change and a marginal adaptation to the existing framework. This article employs a historical-institutional perspective to help reconcile this debate and further understanding of changes to Alberta's oil sands reclamation policies over the past half century. It traces the factors and outlines the processes which have driven its evolution since 1963 with special attention paid to the 2011 Oil Sands Progressive Reclamation Strategy, the most recent attempt to reform oil sands reclamation policy. The article reveals a complex long-term pattern of policy development in which processes of 'tense layering' of new initiatives on top of old elements resulted in a constantly shifting policy landscape as existing policy instruments and settings were 'stretched' to cover new circumstances but failed to resolve tensions between successive policy layers. After 1993, however, a more reflective process was put into place in which policy feedback informed alterations intended to reduce or remove tensions between successive layers. Such a policy 'patching' process is shown to have helped resolve tensions associated with earlier stretching of the existing regime and adds to the vocabulary of more general studies of policy dynamics.